Comparison of the Postoperative Analgesic Effects between Ultrasound-Guided Transmuscular Quadratus Lumborum Block and Thoracic Paravertebral Block in Laparoscopic Partial Nephrectomy Patients: A Randomized, Controlled, and Noninferiority Study - Jin Wang; Xulei Cui; Liying Ren; Xu Li; Yuelun Zhang; Yi Xie; Zhigang Ji; Yuguang Huang (Pain Research and Management)
Background. This prospective, randomized, double-blinded, noninferiority study aimed to compare the effects of analgesia and recovery between transmuscular quadratus lumborum block (TMQLB) and paravertebral block (PVB). Methods. Sixty-eight, American Society of Anesthesiologists level I–III patients, who underwent laparoscopic partial nephrectomy in Peking Union Medical College Hospital were randomly allocated to either TMQLB or PVB group (independent variable) in a 1 : 1 ratio. The TMQLB and PVB groups received corresponding regional anesthesia preoperatively with 0.4 ml/kg of 0.5% ropivacaine and follow-up at postoperative 4, 12, 24, and 48 hours. The participants and outcome assessors were blinded to group allocation. We hypothesized that the primary outcome, postoperative 48-hour cumulative morphine consumption, in the TMQLB group was not more than 50% of that in the PVB group. Secondary outcomes including pain numerical rating scales (NRS) and postoperative recovery data were dependent variables. Results. Thirty patients in each group completed the study. The postoperative 48-hour cumulative morphine consumption was 10.60 ± 5.28 mg in the TMQLB group and 6.40 ± 3.40 mg in the PVB group. The ratio (TMQLB versus PVB) of postoperative 48-hour morphine consumption was 1.29 (95% CI: 1.13–1.48), indicating a noninferior analgesic effect of TMQLB to PVB. The sensory block range was wider in the TMQLB group than in the PVB group (difference 2 dermatomes, 95% CI 1 to 4 dermatomes, P=0.004). The intraoperative analgesic dose was higher in the TMQLB group than in the PVB group (difference 32 µg, 95% CI: 3–62 µg, P=0.03). The postoperative pain NRS at rest and on movement, incidences of side effects, anesthesia-related satisfaction, and quality of recovery scores were similar between the two groups (all P > 0.05). Conclusions. The postoperative 48-hour analgesic effect of TMQLB was noninferior to that of PVB in laparoscopic partial nephrectomy. This trial is registered with NCT03975296